Evaluating the effects of vanadyl sulfate on biomarkers of oxidative stress and inflammation in renal tissue of rats with diabetes type 2 - Bahmani Fereshteh; Afsharipour Ali-Reza; Manteghie Nastaran; Taghizadeh Mohsen; Mirhashemi Seyyed Mehdi (Universidade de São Paulo, 2020)
Vanadyl sulfate (VS) is an ingredient in some food supplements and experimental drugs. This study was designed to assay the effects of VS on biomarkers of oxidative stress and inflammation in renal tissue of rats with diabetes type 2. 30 male Wistar rats were divided into three equal groups as follow: non-diabetics, non-treated diabetics and VS-treated diabetics. Diabetes type 2 has been induced through high fat diet and fructose in the animals. Diabetic rats were treated with 25 mg/kgBW of VS in water for 12 weeks. At the end of study, glucose and insulin were measured using commercially available kits in serum and biomarkers of oxidative stress and inflammation in renal homogenates of animals were measured by related methods. Compared to controls, glucose and insulin were increased significantly in non-treated diabetic rats (p-value <0.05) that showed the induction of diabetes type 2 in rats. The results showed that in VS-treated diabetic rats compared to the non-treated diabetic group, vanadyl sulfate significantly reduced the glucose and insulin secretion and changed renal inflammatory and oxidative markers, except protein carbonyl so that we couldn't find any significant changes. Our study showed that vanadyl supplementation had positive effects on oxidative stress and inflammation biomarkers in kidney of diabetic rats.